Modern radio production - Hausman, Carl (Thomson Wadsworth, 2007)
MODERN RADIO PRODUCTION is a current, comprehensive look at radio production and programming that integrated cutting-edge technologies with explanations of traditional equipment and practices. A clear writing style, excellent descriptions and explanations, and attention to detail make this book easy to read and study from